2021
DOI: 10.3390/en14237864
|View full text |Cite
|
Sign up to set email alerts
|

Social and Economic Value in Emerging Decentralized Energy Business Models: A Critical Review

Abstract: In recent years, numerous studies have explored the opportunities and challenges for emerging decentralized energy systems and business models. However, few studies have focussed specifically on the economic and social value associated with three emerging models: peer-to-peer energy trading (P2P), community self-consumption (CSC) and transactive energy (TE). This article presents the findings of a systematic literature review to address this gap. The paper makes two main contributions to the literature. Firstl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 62 publications
(193 reference statements)
0
11
0
Order By: Relevance
“…However, Scuri et al [120] found that economic incentives do not appear to be a strong motivator for P2P energy trading. Participants in the PowerShare application P2P energy trading can develop new and existing social relationships through the sharing/trading of electricity within communities [32]. A sense of community was perceived by participants at three pilot sites in Portugal to be enhanced by P2P energy sharing activities [121].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Scuri et al [120] found that economic incentives do not appear to be a strong motivator for P2P energy trading. Participants in the PowerShare application P2P energy trading can develop new and existing social relationships through the sharing/trading of electricity within communities [32]. A sense of community was perceived by participants at three pilot sites in Portugal to be enhanced by P2P energy sharing activities [121].…”
Section: Discussionmentioning
confidence: 99%
“…As prosumers have control over setting the transaction terms and delivery of goods and services [8,13], the benefits they can harvest by participating in P2P trading are expected to be significant [31]. This concept provides benefits to the locality in which it operates, such as employment and investment in community assets [32]. Such a model can promote the use of renewable energy in energy communities such as cooperatives that allow residents to collectively benefit from renewable energy systems [33].…”
Section: Literature Review 21 Trends and Policies Toward P2pmentioning
confidence: 99%
“…The potential to maximise social value from clean energy investment is central to justifications for local government action. The concept of 'social value' offers a means to delineate expected co-benefits, but it remains subject to different interpretations, depending on interests and contexts, resulting in a degree of fluidity and ambiguity [19][20][21]. There is also long-standing debate about how to assign value to societal benefits, and whether these need to be quantifiable in order to govern decision making [22].…”
Section: Realising Social Value In Local Decision Making Of Clean Ene...mentioning
confidence: 99%
“…This aids the understanding of options for allocating responsibilities for governing change at differing scales and potential to customise transitions to locations. A place-specific perspective also considers the uneven processes and path dependencies which have particular local impacts related to differences in location and landscapes [28]; a distinctive example is the emergence of low carbon clean-tech clusters in the Ruhr Valley, Germany (see: [19,30]). "Place-specific" and "locally led" planning and action are customised to local interests, priorities and circumstances, rather than the implementation of centralised decisions.…”
Section: The Value Of Place-specific Local Energy Systemsmentioning
confidence: 99%
“…While there is evidence in the literature on the technical aspects of P2P energy trading and some evidence from the global South, such as India (Singh et al, 2017(Singh et al, , 2018, there is still limited evidence from Africa on the socio-economic aspects, such as consumers' inclination to participate in such systems and the importance of financial benefits for engaging in energy trading. For example, the structured literature review by Adams et al (2021) found only one study on the social and economic value produced by P2P in Africa.…”
Section: Benefits Of P2p Energy Tradingmentioning
confidence: 99%